Envy Freeness in Experimental Fair Division Problems - Dorothea K. Herreiner; Clemens Puppe (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
In the recent experimental literature several social preference models have been suggested that address observed behavior not reducible to the pursuit of self-interest. Inequality aversion is one such model where preferences are distributional. Frequently, envy is suggested as the underlying rationale for inequality aversion. Envy is a central criterion in the theoretical literature on fair division, whose definition (Foley 1967) differs from the more casual use of the word in the experimental literature. We present and discuss results from free-form bargaining experiments on fair division problems where the role of envy in Foley's sense can be analyzed and compared to social preferences. We find that envy freeness does matter as a secondary criterion.
Keywords: D63; C91; C78; A13; 330; Fairness; Envy Freeness; Social Preferences; Bargaining